Ethical Challenges Related to the Novel Coronavirus (COVID-19) Outbreak: Interviews With Professionals From Saudi Arabia - Alahmad, Ghiath; Richi, Hanie; BaniMustafa, Ala'a; Almutairi, Adel F. (Frontiers in Medicine, 2021)
The new and dangerous coronavirus disease (COVID-19) has posed a serious challenge to the ability of healthcare systems of many countries to contain the spread of the disease and to mitigate its various consequences. The disease posed many ethical challenges both in itself and in the methods used in its management. Although the ethical principles that healthcare operates under are universal, a thorough understanding of the ethical difficulties it poses necessitates consideration of contextual, societal, and cultural factors. This study provides an in-depth exploration of the ethical challenges related to the COVID-19 pandemic outbreak in relation to healthcare providers, medical researchers, and decision-makers in Saudi Arabia. Four themes were extracted from participants' responses, namely, ethical challenges about disease-control measures, challenges to actions in certain groups, challenges regarding software programs, and finally ethics in research practices. Each theme likewise contained sub-themes. The themes and sub-themes were discussed in light of the ethical principles: autonomy, beneficence, non-beneficence, and justice, as well as other principles, such as protecting confidentiality, privacy, and preventing stigma and discrimination.